Sosialisasi dan Implementasi Sistem Penerangan Tenaga Surya untuk Mendukung Penerangan Lingkungan pada Kawasan Permukiman RW06 Cipedak - Irmayani Irmayani; M. Febriansyah; M. Fadhly Abdillah; Edy Supriyadi; Fivit Marwita; Riadi Marta Dinata; Moh. Azhar; Heru Abrianto (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Environmental lighting is an important public facility that supports community activities and comfort, particularly during nighttime. In RT 04/RW 06 Cipedak Village, several areas require additional lighting due to limited illumination conditions, the presence of trees, road curves, and motorcycle access routes connecting the residential area with surrounding locations. This Community Service Program aimed to conduct socialization and implementation of a solar-powered lighting system as an alternative environmental lighting solution based on renewable energy. The implementation method consisted of field surveys, community socialization regarding the concept and utilization of solar-powered lighting technology, determination of installation points, installation of lighting units, functional testing, and handover of the system to local community representatives. The implemented system consists of solar panels, energy storage batteries, solar charge controllers, automatic light sensors, and LED lamps. The results showed that solar-powered lamp units were successfully installed at priority locations within RT 04/RW 06 Cipedak Village. Functional testing indicated that all installed units operated properly and automatically according to environmental lighting conditions. The socialization activity provided knowledge to the community regarding the utilization of solar energy as an alternative power source for lighting systems, especially in open areas with sufficient sunlight exposure. This activity is expected to encourage the wider adoption of simple and sustainable renewable energy technology in residential environments.